Penyakit Adamantiades-Behcet Koinfeksi dengan Herpes Genital - Korompis, Charly M. M.; Sengkey, Triomega F. X.; Gaspersz, Shienty; Niode, J. (Jurnal Biomedik : JBM, 2018)
Abstract: Adamantiades-Behcet (AB) disease is a rare multi-systemic inflammatory disorder with unknown cause. It is characterized by recurrent mucocutaneous ulcer in the mouth and genitalia, and mostly affects the age group of 20 to 30 ys. Genital lesion of AB must be differentiated from others caused by sexually transmitted disease, such as genital herpes. Co-infection of AB with genital herpes is very rare. We reported a male 72-year old, came with painful ulcers in the mouth and genital area since a week before visit. Symptoms were recurrent since three years ago. History of arthritis, recurrent headache, eye and skin lesions were denied. Patient was sexually promiscuous. Physical examination revealed multiple ulcers on the labium oris sized 0.5cm-1cm, irregular border, base covered by fibrin tissue, associated with erosion and crust. Multiple ulcers were also found on penile glans, sized 0.1x1x0.2 cm, irregular border, with pus and necrotic tissue. The ulcers were punched out. Pathergy test and anti HSV-1 IgM were negative meanwhile anti HSV-1 IgG, anti HSV-2 IgM as well as anti HSV-2 IgG were positive. Acyclovir 200mg 5x/day for five days, triamcinolone acetonide lotion bid for the mouth ulcer, NaCl 0,9% dressing applied tid for 30 minutes, and fucidic acid cream bid were given and the symptoms improved after 10 days. The prognosis was bonam for ad vitam and dubia for ad functionam and ad sanationam. Conclusion: The diagnosis of AB was based on the International Criteria for Behcet Disease, with a total score of 4 for the recurrent ulcer in mouth and genital area. The positive result of anti HSV-1 IgG, anti HSV-2 IgM and anti HSV-2 IgG supported the coinfection with genital herpes. This coinfection of AB and genital herpes was the first reported in Manado. Immunosenescence was a possible risk factor of the recurrent genital herpes. Symptomatic and antiviral treatment improved the symptoms with possible recurrent genital herpes.Keywords: Adamantiades-Behcet, genital herpes, coinfectionAbstrak: Penyakit Adamantiades-Behçet (AB) merupakan kelainan inflamasi multisistemik yang tidak diketahui penyebabnya dengan manifestasi mukokutan tersering berupa ulkus berulang pada mulut dan genital. Penyakit ini terutama terjadi pada usia 20-30an. Lesi genital pada AB perlu dibedakan dengan ulkus genital akibat infeksi menular seksual termasuk herpes genitalis. Koinfeksi AB dan herpes genitalis jarang terjadi. Kami melaporkan kasus seorang laki-laki, usia 72 tahun, dengan keluhan luka di bibir dan kelamin yang nyeri sejak 1 minggu lalu, bersifat hilang-timbul selama 3 tahun terakhir. Riwayat nyeri sendi, sakit kepala berulang, serta kelainan kulit disangkal. Terdapat riwayat promiskuitas yang tinggi. Pada pemeriksaan fisik di regio labialis oris ditemukan ulkus multipel, diameter ±0,5-1 cm, tepi tidak teratur, dasar tertutup jaringan fibrin, dengan erosi dan krusta. Di regio glans penis ditemukan ulkus multipel, ukuran bervariasi ± 1x2x0,2cm, tepi tidak teratur, dasar tertutup pus dan jaringan nekrotik, terdapat punch out dan erosi. Tes patergi negatif. Pemeriksaan anti HSV-1 IgM (-), anti HSV-1 IgG (+), anti HSV-2 IgM dan IgG (+). Terapi asiklovir 5 x 200 mg/hari selama 5 hari, salep triamsinolon asetonid 2 kali oles, kompres terbuka NaCl 0,9% 3 x30 menit/hari, krim asam fusidat 2 kali oles, memberikan perbaikan klinis setelah 10 hari pengobatan. Prognosis quo ad vitam bonam, quo ad functionam, quo ad sanationam ad dubia. Simpulan: Pada kasus ini, diagnosis AB ditegakkan berdasarkan International Criteria for Behcet Disease yaitu ditemukannya ulkus berulang di mulut dan di genital, masing-masing mendapat nilai 2, sehingga nilai total ialah 4. Ditemukannya anti HSV-1 IgG, anti HSV-2 IgG dan IgM positif, menunjang diagnosis tambahan herpes genital (rekuren). Koinfeksi AB dengan herpes genital baru pertama kali dijumpai di Manado. Keadaan immunosenescence kemungkinan menjadi faktor pencetus terjadinya rekurensi herpes genital. Pasien sembuh dengan terapi simtomatis dan antivirus, meskipun kemungkinan rekurensi dapat terjadi lagi.Kata kunci: Adamantiades-Behcet, herpes genital, koinfeksi